Measuring the Role of Leadership Style and Decision Making in Creating Performance - Ris Akril Nurimansjah; Donny Dharmawan; Ratnawita Ratnawita; Loso Judijanto; Sugeng Karyadi (Yayasan Riset dan Pengembangan Intelektual, 2023)
This study aims to investigate the influence of leadership style and decision-making on the performance of employees at Dealer Honda Semarang Center. Employing a quantitative methodology and survey approach, the study selected participants through proportional random sampling, resulting in a sample size of 71 responses. Data analysis was conducted using SPSS version 26, employing multiple regression, t-test, and F-test techniques. The findings revealed positive regression coefficients for both decision-making (X2) and leadership style (X1) variables in relation to performance (Y), indicating a beneficial impact on performance. Specifically, leadership style (X1) demonstrated a partial influence on performance, while decision-making (X2) showed a significant impact. The study concludes that both leadership style and decision-making variables collectively account for 43.5% of the variation in performance, with the remaining percentage attributed to unexplored factors.